Monitoring trade in plastic waste and scrap - Brown, Andrew (OECD Publishing, 2022)
Trade in plastic waste and scrap plays a potentially important role in helping to strengthen markets for recycled plastics as it can help to achieve economic efficiency through for instance economies of scale. But such trade has also been criticised for leading to plastic pollution when recipient countries lack capacity to treat such waste in an environmentally sound manner. This report aims to identify and assess trends in trade patterns of plastic waste and scrap in the context of recent policy developments, particularly the strengthening of controls applied in the context of the Basel Convention, which came into force at the beginning of 2021. One of the findings is that OECD Member Countries continue to make up a significant share of global trade in plastic scrap and waste (89% of global reported exports and 67% of global reported imports by weight), but that the trade surplus has continued to shrink, as well as the overall volume of trade
Keywords: Environment